2010
DOI: 10.1177/1479972309354690
|View full text |Cite
|
Sign up to set email alerts
|

Review series: Occupational and environmental lung disease: Chronic obstructive pulmonary disease and the workplace

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disease associated with increasing morbidity and mortality worldwide. Whilst tobacco smoking is the important cause, other causes are recognized. This article discusses the contribution that harmful inhaled occupational exposures make to the overall burden of COPD, and goes on to discuss other aspects of the COPD workplace interface. Prevention is key. All healthcare professionals have a responsibility to consider workplace issues when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Estimates suggested that more than 20% of instances of COPD in 2010 were attributable to occupational exposure 20. An additive effect of smoking and occupational exposure was seen, increasing the risk for COPD 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates suggested that more than 20% of instances of COPD in 2010 were attributable to occupational exposure 20. An additive effect of smoking and occupational exposure was seen, increasing the risk for COPD 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that 16.3% of all adult-onset asthma is caused by occupational exposure 3 ) . Although smoking is a representative COPD risk factor, a number of studies have addressed the contribution of occupational exposure to COPD 7 , 8 , 9 , 10 , 11 ) . Several studies have shown that the population fraction of COPD attributable to occupational exposure is 15–20% 8 , 12 , 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A signifi cant part of the literature accumulated over the past two decades demonstrated the relationship between vapour, gases, dust, and fumes (VGDF) and the development of COPD (7)(8)(9)(10)(11)(12)(13). However its importance remains underappreciated, especially in the Russian Federation.…”
mentioning
confidence: 99%